2019
DOI: 10.1002/adhm.201970020
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration: Long‐Term Prevention of Bacterial Infection and Enhanced Osteoinductivity of a Hybrid Coating with Selective Silver Toxicity (Adv. Healthcare Mater. 5/2019)

Abstract: In article number https://doi.org/10.1002/adhm.201801465 by Wenbo Jiang, Shuilin Wu, Yongqiang Hao, and co‐workers, HA/Ag/CS coatings are designed to prevent biofilm formation and enhance osteoinductivity of Ti implants. Organic chelators CS and PDA are used to reduce the rapid silver ion release from AgNPs. Due to the double chelating effect of PDA and CS, the coating exhibits excellent antibacterial effects with good osteogenic performance and longitudinal biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In previous studies, it has been shown that silver ions can bind to proteins or DNA of mammalian cells and produce reactive oxygen species in the microenvironment, which leads to cell death or apoptosis (Hsin et al, 2008). Also, the biological toxicity of silver ions is dose dependent, the design strategy to control their cellular and tissue toxicity may be to enable the silver-containing coating on the implant surface to provide controllable release of silver ions (Xie et al, 2019). In our previous study, we showed that nanoscale TiN/Ag multilayers with a smaller modulation period had excellent mechanical properties and cellular compatibility (Sun et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been shown that silver ions can bind to proteins or DNA of mammalian cells and produce reactive oxygen species in the microenvironment, which leads to cell death or apoptosis (Hsin et al, 2008). Also, the biological toxicity of silver ions is dose dependent, the design strategy to control their cellular and tissue toxicity may be to enable the silver-containing coating on the implant surface to provide controllable release of silver ions (Xie et al, 2019). In our previous study, we showed that nanoscale TiN/Ag multilayers with a smaller modulation period had excellent mechanical properties and cellular compatibility (Sun et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…◯ ⊙ [68,127,210] ◯ Nb 1)Enhances the activity and mineralization of human osteoblasts and has little cytotoxicity when supplemented in vitro.…”
Section: ◯ ◯ ◯mentioning
confidence: 99%
“…[ 50,165–168 ] The dual chelating effect of PDA and chitosan has been demonstrated to significantly reduce Ag ion release with excellent antibacterial effect toward S. aureus , S. epidermidis , and E. coli ( Figure ). [ 171 ] The pH level at the peri‐implant during bacterial infection is reduced to as low as 5.5. A pH‐sensitive coating consisting of AgNPs and acetal linker has been fabricated and the Ag ion is released at low pH when bacterial infection occurs.…”
Section: Ion‐incorporated Coating On Ti For Enhanced Osteogenic and Amentioning
confidence: 99%